Amelioration of High Fat Diet-induced Glucose Intolerance by Blockade of Smad4 in Pancreatic Beta-Cells - Li, H. Y.; Oh, Y. S.; Lee, Y.-J.; Lee, E.-K.; Jung, H. S.; Jun, H.-S. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Background: In this study, we investigated whether Smad4 signaling is involved in the regulation of beta-cell function using a high fat diet (HFD)-induced obesity mouse model.Methods: Beta-cell-specific Smad4-knockout mice (Smad4-/-RIP-Cre+; β-Smad4KO) were generated by mating Smad4 (flox/flox) mice with rat insulin promoter (RIP)-Cre mice. Mice were fed a HFD beginning at 6 weeks of age for 16 weeks. Body weight, food intake, fasting and fed glucose levels, and glucose and insulin tolerance were measured.Results: The expression of Smad4 mRNA was significantly decreased in the islets of β-Smad4KO mice. In wild-type mice, Smad4 mRNA was significantly decreased at 18 weeks of age as compared with 8 weeks of age. On a regular chow diet, β-Smad4KO mice showed no differences in body weight, fed and fasting blood glucose levels, and glucose tolerance compared with wild-type mice. When fed a HFD, body weight gain was significantly reduced in β-Smad4KO mice as compared with wild-type mice, although the amount of food intake was not different. During the HFD, fed and fasting blood glucose levels, glucose stimulated insulin secretion, disposition index and glucose tolerance were significantly improved in β-Smad4KO mice as compared with wild-type mice. However, insulin tolerance tests showed no differences between the 2 groups.Conclusion: Inhibition of Smad4 in beta-cells conferred mild but significant improvements in glucose levels and glucose tolerance in HFD-induced obese mice. Therefore, regulation of Smad4 expression may be one of the mechanisms regulating physiological expansion of beta-cells during development of type 2 diabetes.
Keywords: Type 2 diabetes; pancreatic beta-cell; high-fat diet-induced obesity; beta-cell-specific Smad4-knockout mice; transforming growth factor-β; smad4; glucose tolerance